NEW WAYS OF LEARNING TO OF TEACH MATHEMATICS: FORMATIVE EXPERIENCES WITH PEDAGOGY STUDENTS - Jaqueline de Souza Pereira Grilo; Wedeson Oliveira Costa (Universidade do Estado do Rio de Janeiro (UERJ), 2023)
The article shares the results of a research that aimed to describe the formative experiences shared with Pedagogy students who were involved in "new ways of learning" to teach mathematics. The data were produced through a qualitative approach that investigated the pedagogical practice established between teachers and students in curricular components that deal with the Fundamentals of Mathematics in the Degree in Pedagogy and the reports of the students' formative experiences in this component. Therefore, the production of data based the on observations of pedagogical practice and on interviews with the students after completing the curricular component. The data showed that the "new ways of learning" to teach mathematics privilege the articulation between theory and practice, focusing on the use of manipulative materials and the construction of different solutions, in order to expand the students' repertoire regarding the strategies that can be used when teaching numbers and operations that turn to mathematical investigations and explorations that allow the resignification of contents